Ricín--rastlinný toxín s mozným terapeutickým vyuzitím - Nagy, M (Ceska a Slovenska farmacie, 2004)
Ricin is a very toxic RIP II type lectin. As no effective antidote is known, its toxicity could be misused in terrorist actions. The mechanism of the toxic action is currently studied for the preparation of selective immunotoxins, which could be used in the therapy of various cancer diseases or HIV infection. There are promising in vitro results, but some adverse in vivo effects limit the use of these preparations in real therapy.
Keywords: Animals; lidé; imunotoxiny; ricin; Immunotoxins; Humans; Ricin; zvířata